Faktor Yang Mempengaruhi Variasi Titer Anti Hbsag Pada Post Pemberian Vaksin Hepatitis B Pada Pasien Ckd On Hd Di Rumah Sakit Premier Surabaya - Any Crisanty (2015)
Hemodialisis patients are very susceptible to infection, which can decrease in immune response. Variations titers Anti HBSAg thatoccur in patientswhoroutinelyrun Hemodialysisfollowing administration ofhepatitis B vaccinecouldbean increase, decreaseor negativeantibodies. Variationsrespon immune of antibodiesin patients withCKDwho receivedHepatitisBvaccineat this timeis influencedbyseveralfactors such as:increased levels ofurea, albumin, increased levels offerritin, andadequacy ofHD.The aims of this studywas to determinethe factorsthat influencevariationsof Anti-HBsAg titers whichincreasein CKD patientswhoundergoroutineHemodialysisinPremier Hospital. Thisresearchusesdescriptive method, by correlation analyzingdatabetweenelevated levels ofurea, albumin, increased levels offerritin, andadequacy ofHD. Descriptivecorrelation designwas used in this study with crosssectionalapproach analytical,the number of hemodialysis patientsinPremier Hospitalas many as36people. The population inthis studywere23 patients undergoingregularHemodialysisinPremier SurabayaHospital whomet to the inclusion criteria.Resultusing purposive sampling technique. Researchers conducted alaboratoryanalysis of the resultsofurea,Anti HBSAg, ferritin, albuminin MaytoAugust,andanalyzedthe factorsthat influencevariation ofAnti HBSAg. Result of this study showed significant corelation beatween levels of urea in HD patients was very influential in the variation of Anti HBSAg post Hepatitis B vaccine with p=0,28, significan level<5%, there were corelation beatween variation of Anti HBSAg and feritin level with p=0,040 , significan level<5%, there were corelation beatween variation of Anti HBSAg and Albumin level with p=0,326 , significan level<5%, there were corelation beatween variation of Anti HBSAg and adekuasi HD level with p=0,285, significan level<5%, The conclution of this research was that the significant corelation exists between increased levels ofurea, albumin, increased levels offerritin, andadequacy ofHD on variationsof antibodiesin patients withCKDwho receivedHepatitisBvaccine pasient.